Liberalizing the Nuclear Energy Sector: Small Modular Reactors, Net-Zeros, and Perceptions in India - Hely Desai (International Journal of Nuclear Security, 2025)
The experimental small modular reactors (SMRs) have come to gain immense attention and importance given the global quest to quickly achieve net-zero goals. The Indian Government, too, has been pushing for SMRs to aid its industrial decarbonization targets and eventually wield the supply mediation in the race to acquire this novel technology. However, one of the key debates driving SMR discourse in India is the dilemma of allowing the involvement of the private sector into the nuclear energy realm. Although this idea seems to be an exciting solution to India’s energy woes, the reevaluation of a 60-year-old energy law comes with a new set of security challenges and financial opportunities for New Delhi regarding the manufacturing and deployment of these new state-of-the-art reactors. This paper analyzes the efficacy of incorporating SMRs into India’s energy mix and if it would be more advantageous to allow private investments into the nuclear energy sector. This research studied India’s energy laws and traced its amendments and shortcomings over the years. Although leveraging the private entities may prove to be beneficial in providing cost-effective and smooth grid-adjustment fixes for the nuclear energy sector, the method will face major structural and security challenges and will require an extensively elaborate technology-neutral policy framework with a focus on green taxonomies, as well as a pivot around societal acceptance. There has not been much research conducted on the idea of commencing private involvement in the Indian nuclear energy sector apart from a few NITI Aayog reports and a few trivial opinion pieces in the print media. This study used archival policy reports, government documents, parliamentary discussions, and interviews of officials at the intersection of science and policy as sources to build an elaborate policy report on how beneficial the incorporation of private entities into the nuclear sector would be. Although SMRs have been on the policy lineups for almost a decade now, they have not translated into a practical commercial option. This research tried to investigate if allowing private players would benefit the quick deployment of SMR technology and, in turn, help to fulfill India’s commitment to chart its way to becoming net-zero by 2070.
Keywords: Small Modular Reactors; Energy Laws; Net Zero; Climate; Nuclear Energy; Private Investments